2017
DOI: 10.1111/jmg.12257
|View full text |Cite
|
Sign up to set email alerts
|

High‐ to ultrahigh‐temperature metamorphism in the lower crust: An example resulting from Hikurangi Plateau collision and slab rollback in New Zealand

Abstract: Lower crustal xenoliths erupted from an intraplate diatreme reveal that a portion of the New Zealand Gondwana margin experienced high‐temperature (HT) to ultrahigh‐temperature (UHT) granulite facies metamorphism just after flat slab subduction ceased at c. 110–105 Ma. P–T calculations for garnet–orthopyroxene‐bearing felsic granulite xenoliths indicate equilibration at ~815 to 910°C and 0.7 to 0.8 GPa, with garnet‐bearing mafic granulite xenoliths yielding at least 900°C. Supporting evidence for the attainment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 96 publications
1
14
0
Order By: Relevance
“…If this region of widespread extension encompassed the Alpine Schist, it is possible that associated rise of the hot upper mantle underneath the accretionary complex could have driven diachronous garnet growth in the Alpine Schist. This explanation was proposed by Jacob et al (2017) for the HT to UHT metamorphism observed in lower crustal xenoliths from the base of the accretionary complex in the Otago Schist region.…”
Section: Tectonic Implicationsmentioning
confidence: 76%
See 3 more Smart Citations
“…If this region of widespread extension encompassed the Alpine Schist, it is possible that associated rise of the hot upper mantle underneath the accretionary complex could have driven diachronous garnet growth in the Alpine Schist. This explanation was proposed by Jacob et al (2017) for the HT to UHT metamorphism observed in lower crustal xenoliths from the base of the accretionary complex in the Otago Schist region.…”
Section: Tectonic Implicationsmentioning
confidence: 76%
“…The Lu–Hf garnet ages from WC14‐01 (97.3 ± 0.3 Ma) and WC14‐38 (91.8 ± 0.3 Ma) overlap with the Sm–Nd age of 100 ± 12 Ma from a nearby garnet amphibolite at Haast River (Mortimer & Cooper, ). Additionally, the WC14‐38 garnet age is consistent with the timing of high‐temperature (HT) to ultrahigh‐temperature (UHT) metamorphism of the lower crust beneath the Otago Schist, dated at 91.7 ± 2 Ma using zircon from granulite xenoliths contained within the Kakanui Mineral Breccia (Jacob, Scott, Turnbull, Tarling, & Sagar, ). Although these xenoliths are located 200 km from the location of WC14‐38, it is possible that high‐grade metamorphism in these regions was driven by the same regional heating event, such as conductive heating of the lower crust by hot upper mantle, as suggested by Jacob et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2) (Mortimer, 2004). Unlike formerly contiguous Antarctica and Australia, neither surficial nor deeply exhumed crust (e.g., Beyssac et al 2015;Jacob et al, 2017) or zircon U-Pb-Hf isotope systematics in igneous rocks (e.g., Bolhar et al, 2008) provide evidence that Zealandia has an Archean or even Proterozoic crustal core.…”
Section: Zealandia's Geological Contextmentioning
confidence: 98%